Maximizing donors' gifts: A comparison of actual and expected solid organ yield among VCA donors. Issue 3 (13th October 2020) - Vece, Gabriel R.; Robinson, Amanda; Rosendale, John; Cherikh, Wida; Curran, Christopher; Wholley, Christopher; DiBatista, Darren; Klassen, David; Wainright, Jennifer
Abstract : Vascularized Composite Allograft (VCA) transplantation provides life‐changing transplants, but VCA adds complexity to the donation process and timing, possibly impeding solid organ donation. Expanding upon descriptive analyses, this study examines risk‐adjusted predictions versus the observed number of organs donated by VCA donors. Our cohort included VCA donors in the United States during January 1, 2008–December 31, 2017 (n = 51), using OPTN Deceased Donor Registration Form data and the Scientific Registry of Transplant Recipients (SRTR) donor yield models to calculate observed‐to‐expected (O:E) yield ratios. Almost all VCA donors' livers (48/51; 94.1%) and kidneys (92/102; 90.2%) were transplanted, with fewer hearts (28/51; 54.9%), lungs (46/102; 45.1%), pancreata (15/51; 29.4%), and intestines (3/51; 5.9%) transplanted. O:E ratios for overall organ yield were slightly greater than expected for VCA donors (1.10; 95% CI: 1.02–1.17). Liver (1.17: 1.08–1.27) and lung yields (1.38: 1.07–1.68) were both greater than expected, while kidney, heart, and pancreas yields were similar to expected. Across VCA types, bilateral upper limb and abdominal wall donors had better‐than‐expected yields while uterus, face, and unilateral upper limb donors all had similar‐to‐expected yields. Solid organ yield among VCA donors was as good or better than predicted, suggesting that VCA donation does not compromise recovery and transplantation of lifesaving organs. Abstract : Risk‐adjusted analyses of national data show that, for donors of vascularized composite allografts, the observed yield of each solid organ was either equivalent to (kidney, heart, and pancreas) or better than (liver and lung) the predicted yield.